Seroprevalence, and Risk Factors of Post-Vaccination Antibodies for Foot and Mouth Disease in Tanah Laut District, South Borneo in 2022-2023 - Adrin Ma'ruf; Heru Susetya; Tri Untari; Elfa Zuraida (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2023)
Foot and Mouth Disease (FMD) caused by the Foot Mouth Disease virus (FMDV) is an animal disease that spreads quickly and causes huge economic losses. The Indonesian government has established the vaccination program as a form of national FMD management in 2022. This study was conducted to determine the success and post-vaccination seroprevalence of FMD in Tanah Laut District, South Borneo, and to analyze the factors that influence the success of vaccination. The research method is observational analytic with a cross-sectional study approach. Samples were sera of cows and goats that had been vaccinated, then tested serologically with SP ELISA serotype O and NSP ELISA. Result analyzed by chi-square test (X2), odds ratio (OR), relative risk (RR), and spatial analysis (average nearest neighbor).The seroprevalence of immunity to FMD in Tanah Laut Regency was 95.94%. Factors that influence the formation of antibodies after FMD vaccination were the type of animal (OR = 3.781), age (OR = 6.106), sex (OR = 2.801), rearing system (OR = 3.848), feed (OR = 3.448), type of vaccine (OR = 5.508), and number of vaccinations (OR = 0.109). Spatial analysis shows a clustered pattern (Nearest Neighbor Ratio = 0.005457). The seroprevalence of immunity to FMD in Tanah Laut Regency was 95.94%. Goat immune seroprevalence has a higher value when compared to cattle. Factors that influence the formation of FMD vaccination antibodies are animal type, age, sex, feed, rearing system, type of vaccine, and number of vaccinations.